PENGGUNAAN PENDEKATAN SATIR PADA IKLAN AXIS #KENAPANGGAK - indah wenerda (Jurnal Ranah Komunikasi, 2018)
Media is one of the tools that helped shape how cultural practices develop in the midst of human life, one of which is through advertising. This can be the opposite, developing cultural practices also contribute to how advertising in this case are produced by advertisers. In the #KenapaNggak Axis Ad, which was just released in early May, it displays the realities that are happening in today's society, especially the character of today's young people. This reality is packaged in such a way by ad makers through Axis Ads #KenapaNggak. This paper is made using qualitative research. This type of research understands the phenomenon in the subject of research by describing it in the form of words and language. In this study the author will describe the form of the satirical approach used by advertisers on Axis Ads #KenapaNggak. Axis ads are consistent since 2008 making their advertisements by not displaying the shortcomings of other providers as competitors. Rather it displays something that is still relevant to the function or usefulness of the product. The method used is to use a humorous approach that is conveyed satire. The visualization displayed through visual slice of life, life style, and personality symbols, which were then combined into one on the Axis Ad #KenapaNggak is a form of mockery of producers to today's audiences as super active internet users.